POM Anolyte for All‐Anion Redox Flow Batteries with High Capacity Retention and Coulombic Efficiency at Mild pH. Issue 7 (9th January 2022) - Yang, Le; Hao, Yahui; Lin, Jiande; Li, Ke; Luo, Siheng; Lei, Jie; Han, Yanhong; Yuan, Ruming; Liu, Guokun; Ren, Bin; Chen, Jiajia
Abstract: A highly soluble Li5 BW12 O40 cluster delivers 2 e − redox reaction with fast electron transfer rates (2.5 × 10 −2 cm s −1 ) and high diffusion coefficients (≈2.08 × 10 −6 cm 2 s −1 ) at mild pH ranging from 3 to 8. In‐operando aqueous‐flowing Raman spectroscopy and density functional theory calculations reveal that Raman shift changing of BW12 clusters is due to the bond length changing between W‐Ob ‐W and W‐Oc ‐W at different redox states. The structure changing and redox chemistry of Li5 BW12 O40 are highly reversible, which makes the Li5 BW12 O40 cluster versatile to construct all‐anion aqueous redox flow batteries (RFBs). The cation‐exchange Nafion membrane will also repel the cross permeability of the anion redox couples. Consequently, by coupling with Li3 K[Fe(CN)6 ] catholyte, the aqueous RFB can be operated at pH 8 with a capacity retention up to 95% and an average Coulombic efficiency more than 99.79% over 300 cycles within 0 to 1.2 V. Meanwhile, Li5 BW12 O40 cluster can also be paired with LiI catholyte to form aqueous RFBs at pH 7 and pH 3, the capacity retention of 94% and 90% can be realized over 300 cycles within 0 to 1.3 V. Abstract : Due to the multi‐electron redox ability, structure stability, and high redox kinetics of BW12 polyoxometalate (POM) anion anolyte at mild pH, all‐anion aqueous redox flow batteries coupled with different catholyte anion exhibit very high capacity retention. An in‐operando aqueous flowing Raman spectroscopy technique is also first constructed to investigate the structural revolution and stability of POMs anion during battery operation.